The Structure and Development of Science
IX, 293 p.
Keywords: TIus is the second, and fmal, volume to derive from the exciting Kronberg conference of 1975, and to show the intelligent editorial care of Gerard Radnitzky and Gunnar Andersson that was so evident in the first book, Progress and Rationality in Science (Boston Studies in the Philosophy of Science, Vol. 58). Together they set forth central themes in current history and philosophy of the sciences, and in particular they will be seen as also providing obbligatos: research programs, metaphysical inevitabilities, methodological options, logical constraints, historical conjectures. Boston University Center for the R. S. COHEN Philosophy and History of Science M. W. WARTOFSKY July 1979 T T ABLE OF CONTENTS v EDITORIAL EDITORIAL PREFACE PREFACE ix PREFACE PREFACE INTRODUCTION GUNNAR ANDERSSON / Presuppositions, Problems,Progress 3 PART I: METAPHYSICS AND THE DEVELOPMENT OF SCIENCE NICHOLAS RESCHER / Some Issues Regarding the Completeness of Science and the limits of Scientific Knowledge 19 MAX JAMMER / A Consideration of the Philosophical Implications of the New Physics 41 PAUL FEYERABEND / Dialogue on Method 63 PETER HODGSON / Presuppositions and limits of Science 133 PART II: RESEARCH PROGRAMS AND THE DEVELOPMENT OF SCIENCE WOLFGANG STEGMULLER / A Combined Approach to the Dynam ics of Theories. How to Improve Historical Interpretations of Theory Change by Applying Set Theoretical Structures 151 JOSEPH J. KOCKELMANS / Reflections on Lakatos' Methodology of Scientific Research Programs 187 P A TRICK A.